Penggunaan Limbah Abu Batu Sebagai Campuran Pada Agregat Halus Terhadap Kuat Tekan Beton: Use Of Stone Ash Waste As A Mixture In Fine Aggregate On Compressive Strength Of Concrete - Fatwa, Rinaldi; Handayani, Noviyanthy; Faradila, Amelia (Media Ilmiah Teknik Sipil, 2024)
Stone ash is a fine aggregate that passes through sieve no. 4 (diameter 4.75mm) but is retained on sieve no. 200 (0.075mm), thus making stone ash a waste that is useful as a mixture of construction building materials because stone ash can function as a fine aggregate as a substitute for sand in concrete mixtures. The purpose of this research is to find out whether stone ash can be a suitable and good material as a substitute for some of the fine aggregate (sand) in a normal concrete mixture or not, to find out the results of the compressive strength test of concrete by stone ash in a normal concrete mixture, and what percentage composition stone ash which produces optimal concrete compressive strength tests or according to plan. The test object used was a 150 × 300mm cylinder with a total of 36 samples. Stone ash waste with composition ratios of 15%, 25% and 35% has a fairly good bond as an added material to normal concrete mixtures as a substitute for fine aggregate and can even increase the compressive strength of concrete significantly. The composition of stone ash used as a mixture for fine aggregate is 15%, 25% and 35% with a planned concrete quality of 20 MPa and a concrete age of 7, 14 and 28 days. The compressive strength produced by normal concrete without a mixture of stone ash aged 7, 14, and 28 days produces concrete compressive strengths of 13.63 MPa, 19.57 MPa, and 20.53 MPa. Next, for concrete with a rock ash composition of 15% of fine aggregate with an age of 7, 14 and 28 days, the concrete compressive strength is 15.75 MPa, 18.02 MPa, 22.03 MPa. Concrete with a stone ash composition of 25% of fine aggregate with an age of 7.14 and 28 days produces a concrete compressive strength of 15.96 MPa, 19.02 MPa, 21.16 MPa. Concrete with a stone ash composition of 35% of fine aggregate with an age of 7, 14 and 28 days produces a concrete compressive strength of 23.49 MPa, 24.31 MPa, 24.95 MPa. From the research conducted, the 35% composition has the highest compressive strength value of concrete among the other compositions